Analisis Potensi Objek Wisata Alam di Kabupaten Minahasa Utara - Natalino Andreas Ratu; Maxi Tendean; Jolanda Esther Kaihatu (Jurnal Social Science, 2023)
This research aims to determine the physical potential and biophysical potential of natural tourist attractions in North Minahasa district. of the several tourist attractions in the North Minahasa district, the research objects chosen were Paal Beach and Pulisan Beach, East Likupang subdistrict because they are in the Likupang Special Economic Zone, part of the five super priority tourist destinations. The results of the research show that based on the award results, the physical potential in the Paal Beach and Pulisan Beach tourist attraction areas both received 51 awards, which means the level of potential is very high. Thus, Paal Beach and Pulisan Beach are natural tourist attractions that are worthy of being developed and promoted. The results of the biophysical potential assessment obtained a score of 10, which means a perfect score for the biophysical sub-variable. Thus, the existing biophysical potential is very worthy of being promoted and can be a tool to attract tourists to come on tour in the North Minahasa district.